Dynamic assessment of interleukin‐6 during hemodialysis and mortality in coronavirus disease‐19. Issue 6 (2nd February 2021) - Quiroga, Borja; Muñoz Ramos, Patricia; Giorgi, Martin; de Santos, Antonio; Núñez, Almudena; Ortiz, Alberto; Redondo Polo, Concepción; Almería Gómez, Olga; Marcos‐Jiménez, Ana; Esparcia Pinedo, Laura; Barril, Guillermina
Abstract: The impact of the newly discovered severe acute respiratory syndrome coronavirus 2 causing coronavirus disease‐19 (COVID‐19) in hemodialysis patients remains poorly characterized. Some hemodialysis techniques reduce systemic inflammation but their impact on COVID‐19 has not been addressed. The aim of this prospective study was to evaluate factors associated with mortality in COVID‐19 hemodialysis patients, including the impact of reducing interleukin‐6 using a cytokine adsorbent filter. This is a prospective single‐center study including 16 hemodialysis patients with COVID‐19. All were dialyzed using a polymethyl methacrylate (PMMA) filter. Interleukin‐6 levels were obtained before and after the first admission hemodialysis session and at 1 week. Baseline comorbidities, laboratory values, chest X‐ray, and treatments were recorded and compared between survivors and non‐survivors. Out of 16 patients (13 males, mean age 72 ± 15 years), 4 (25%) died. Factors associated with mortality were dialysis vintage ( P  = 0.01), chest X‐ray infiltrates ( P  = 0.032), serum C‐reactive protein ( P  = 0.05), and lactate dehydrogenase ( P  = 0.02) at 1 week, oxygen therapy requirement ( P  = 0.02) and anticoagulation ( P  < 0.01). At admission, non‐survivors had higher predialysis and postdialysis interleukin‐6 levels ( P  = 0.02 for both) and did not present the reduction of interleukin‐6 levels during the dialysis session with PMMA filter that was observed in survivors (survivors vs. non‐survivors: 25.0 [17.5–53.2]% vs. −2.8 [−109.4–12.8]% reduction, P  = 0.04). A positive balance of interleukin‐6 during the admission dialysis was associated with mortality ( P  = 0.008). In conclusion, in hemodialysis COVID‐19 patients, a positive interleukin‐6 balance during the admission hemodialysis session was associated with higher mortality.